Tuber indicum and T. lijiangense colonization differentially regulates plant physiological responses and mycorrhizosphere bacterial community of Castanopsis rockii seedlings - Huang, Lanlan; Li, Yongmei; Yuan, Jing; Wan, Shanping; Colinas, Carlos; He, Xinhua; Shi, Xiaofei; Wang, Yanliang; Yu, Fuqiang (Frontiers in Plant Science, 2023)
Black truffles and white truffles are widely studied around the world, but their effects on plant growth and physiological responses, and on the mycorrhizosphere bacterial community of the host plant remain unclear. Here, mycorrhizal colonization of Castanopsis rockii by Tuber indicum (Chinese black truffle) and T. lijiangense (Chinese white truffle), respectively, was induced in a greenhouse study, and their effects on host growth, physiological responses and mycorrhizosphere bacterial communities were compared. The results show that colonization of both Tuber species significantly increased leaf photosynthetic rate, leaf P concentration and mycorrhizosphere acid phosphatase activity, as well as richness of mycorrhizosphere bacterial communities of C. rockii seedlings. However, T. indicum colonization on the one hand significantly decreased tartrate content, bacterial acid phosphatase, phoC gene abundance in the mycorrhizosphere, and peroxidase (POD) activity of ectomycorrhizal root tips, but on the other hand increased mycorrhizosphere pH and superoxide dismutase (SOD) of ectomycorrhizal root tips, compared to T. lijiangense colonization. Moreover, principal coordinate and β-diversity analyses show significant differences in mycorrhizosphere bacterial community composition between T. indicum and T. lijiangese colonized C. rockii seedlings. Finally, the relative abundance of the bacterium Agromyces cerinus significantly correlated to mycorrhizosphere acid phosphatase activity and leaf P concentration, suggesting that this bacterium might play an important role in P mobilization and acquisition. Overall, these results suggest that T. indicum and T. lijiangense differently regulate their host plant’s physiological responses and mycorrhizosphere bacterial community.